Novel synthesized cationic surfactants based on natural piper nigrum as sustainable-green inhibitors for steel pipeline corrosion in CO2-3.5%NaCl: DFT, Monte Carlo simulations and experimental approaches. (20th March 2020) - Tantawy, Ahmed H.; Soliman, Kamal A.; Abd El-Lateef, Hany M.
Abstract: CO2 -Corrosion is a widespread issue in oil and gas production, and various storage media have different impacts on the corrosion performance of steel used for tubes. In this paper, three novel cationic surfactants based on natural piper nigrum for inhibiting CO2 -corrosion have been synthesized. The structure configurations of the prepared surfactants were confirmed by various spectral and physico-chemical tools viz. FTIR, 1 H NMR, 13 C NMR and surface activity measurements. The measurement of contact angles was used to evaluate the wettability of all synthesized surfactants. The inhibition capacities of the titled surfactants, for steel pipelines (C1018-steel) corrosion in CO2 -3.5%NaCl were studied by electrochemical (open-circuit potential vs. time, Tafel and EIS) measurements, surface morphology (FE-SEM/EDX) examinations, DFT, and Monte Carlo simulations. The empirical findings indicated that the prepared natural surfactants had superior inhibition action, and their maximum inhibition capacities were ranged from 96.7 to 98.9%. Tafel data displays the features of these surfactants are considered as inhibitors of the mixed-type; and their adsorption mode on the C1018-steel/medium interface is consistent with the Langmuir isotherm model. The formation of a protective layer on the C1018-steel interface was investigated using FE-SEM/EDX. DFT calculations were carried out to correlate theoretical parameters with experimental outcomes. The Monte Carlo simulations affirm the adsorption capability of the synthesized surfactants on the iron (110) crystal. The present report provides extremely significative findings in preparing and designing novel sustainable-green inhibitors with high inhibition power. Graphical abstract: Image 1 Highlights: A novel series of cationic surfactants based on natural piper nigrum have been synthesized and characterized. The inhibition characteristics of the prepared surfactants, for steel pipelines corrosion in CO2 -3.5%NaCl were studied. The maximum inhibition capacities were ranged from 96.7% to 98.9%. The potentiodynamic polarization studies indicated that the studied surfactants are mixed type inhibitors. DFT calculations and Monte Carlo simulations showed good correlation with the empirical outcomes.